INDONESIA–THAILAND EXTRADITION COOPERATION: ANALYSIS OF THE 1976 TREATY OF EXTRADITION IN THE ENFORCEMENT OF HUMAN TRAFFICKING LAWS - Arwami, Fitri; Astuti, Mirsa (JCH (Jurnal Cendekia Hukum), 2025)
Human trafficking is a form of transnational organized crime that requires effective international cooperation in law enforcement. One such cooperation mechanism is extradition, as stipulated in the 1976 Extradition Agreement between Indonesia and Thailand, which was ratified through Law No. 2 of 1978. This study aims to analyze the implementation of the extradition treaty between Indonesia and Thailand in handling human trafficking crimes and to identify the obstacles that affect its effectiveness. The research method used is normative legal research with a legislative and conceptual approach. The research data were obtained through a literature study of legislation, legal literature, and relevant research results, then analyzed qualitatively using a descriptive-analytical method. The results of the research show that the implementation of extradition between Indonesia and Thailand still faces various obstacles, including differences in legal systems, administrative constraints, the application of the principle of non-extradition to its own citizens, and differences in human rights protection standards, including those related to the possibility of applying the death penalty. In the context of international law, the refusal of extradition does not eliminate the obligation of the state to prosecute perpetrators based on the Aut Dedere Aut Judicare principle as stipulated in the Palermo Convention. Therefore, it is necessary to strengthen bilateral and regional cooperation, including the optimization of Mutual Legal Assistance and the utilization of ASEAN cooperation mechanisms to increase the effectiveness of combating human trafficking.